Comparison of No-Touch Extubation with Conventional Awake Extubation in Patients Undergoing Tonsillectomy in General Anesthesia - Rizwan, Muhammad; Riaz, Azmat; Ali, Chaudhry Amjad; Ansari, Kaswar Sajjad; Qureshi, Sajjad; Majeed, Kaukab (Pakistan Armed Forces Medical Journal, 2025)
Objective: To compare frequency of side effects between “no-touch” extubation compared with “awake” tracheal extubation. Study Design: Quasi-experimental study. Place and Duration of Study: Department of Anesthesia, Combined Military Hospital, Quetta Pakistan, from Mar to Aug 2023. Methodology: The study began after gaining ethical approval with sample size approximated through online sample size calculator and randomization done to divide patients into two groups, Group N, which underwent “no-touch” extubation and Group A, which underwent conventional awake extubation. The frequency of adverse reactions was noted with both tech-niques and data analysis was performed to compute statistical significance where p-value ≤0.05 was considered significant. Results: Group N had fewer side effects at extubation when compared to Group A with coughing found in only 2(6.7%) and bucking in only 3(10%) patients from Group N. Laryngospam, tongue fall, breath holding and emergence delirium was not reported in any of Group N patients but it was present in 3(10%), 7(23.3%), 4(13%) and 3(10%) patients from Group A. Conclusion: “No-touch” extubation was a better and safer alternative to “awake” extubation in terms of fewer adverse events encountered by patients.